2020
DOI: 10.1186/s40360-020-00444-z
|View full text |Cite
|
Sign up to set email alerts
|

A protein interaction map identifies existing drugs targeting SARS-CoV-2

Abstract: Background: Severe acute respiratory syndrome coronavirus (SARS-CoV-2), an emerging Betacoronavirus, is the causative agent of COVID-19. Angiotensin converting enzyme 2 (ACE2), being the main cell receptor of SARS-CoV-2, plays a role in the entry of the virus into the cell. Currently, there are neither specific antiviral drugs for the treatment or preventive drugs such as vaccines. Methods: We proposed a bioinformatics analysis to test in silico existing drugs as a fast way to identify an efficient therapy. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…In conclusion, we proposed several existing drugs with antiviral activity that, alone or in combination, could be considered as drugs against COVID-19. However, it is vital to better understand the clinicopathological features of COVID-19 to design treatment plans leading to favorable outcomes in SARS-CoV-2 infected patients [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we proposed several existing drugs with antiviral activity that, alone or in combination, could be considered as drugs against COVID-19. However, it is vital to better understand the clinicopathological features of COVID-19 to design treatment plans leading to favorable outcomes in SARS-CoV-2 infected patients [ 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resulting pattern could facilitate the structure-guided pharmaceutical and diagnostic research in order to identify potential new host targets. In addition, Cava et al [ 64 ] reported that the incorporation of drug-gene interactions in the molecular docking analysis is very helpful in finding several drugs with antiviral activity which could be used alone or in combination with other therapeutic options as new therapeutic approaches in the battle against COVID-19 pandemic disease.…”
Section: Main Textmentioning
confidence: 99%
“…While numerous efforts are underway to identify potential therapies targeting various aspects of the disease, there is a paucity of clinically proven treatments for COVID-19. There have been efforts to therapeutically target the hyperinflammation associated with severe COVID-19 4 , as well as to utilize previously identified antiviral medications 5 , 6 . One of these antivirals, remdesivir, an intravenously administered RNA-dependent RNA polymerase inhibitor, showed positive preliminary results in patients with severe COVID-19 7 .…”
Section: Introductionmentioning
confidence: 99%